High female desert tortoise mortality in the western Sonoran Desert during California’s epic 2012-2016 drought - JE Lovich; SR Puffer; K Cummings; TR Arundel; MS Vamstad; KD Brundige (Endangered Species Research, 2023)
We conducted population surveys for desert tortoises Gopherus agassizii at 2 nearby sites in the western Sonoran Desert of California, USA, from 2015-2018, during the driest ongoing 22 yr period (2000-2021) in the southwestern USA in over 1200 yr. We hypothesized that drought-induced mortality would be female-biased due to water and energy losses attributable to egg production during protracted periods of resource limitation. At the higher-elevation, cooler, wetter Cottonwood site from 2015-2016, the sex ratio of live adult tortoises was biased toward males and the sex ratio of tortoises estimated to have died during the intensified drought conditions from 2012-2016 was essentially even. At the lower-elevation, warmer, drier Orocopia site from 2017-2018, the sex ratio of live adult tortoises was biased toward males and the sex ratio of tortoises with estimated times of death from 2012-2016 was biased toward females. High female mortality at the Orocopia site may have resulted from the interaction of drought effects and the bet-hedging reproductive strategy of tortoises wherein they continue to produce clutches of eggs in drought years. Annual reproductive output results in an estimated loss of up to 13.5% of female tortoise body mass including over 0.20 l of water. Combined with dehydration during severe droughts, these losses may compromise their ability to survive droughts lasting more than 2 yr. The low tortoise density and high mortality of females observed may reflect reduced survival of tortoises near the southern edge of their range due to climate change, including protracted and intensified droughts.